Factors that impact the productivity of Malaysian firms in electrical & electronics (E&E) industries: A case study of company ABC - Yap, Carey Zun Xuan; Tham, Pui Ee (2018)
Under Eleventh Malaysia Plan (11MP), manufacturing sector is the core sector that maintains sustainable growth in order for Malaysia to attain high-income country status by 2020. In manufacturing sector, E&E industry is the main driver of this sector that significantly contribute to employment, investments, added value and exports. The government is placing high emphasizing on the significant of productivity as the key driver to sustain the Malaysian economic growth in the long run. Productivity is the key driver of the economic development of Malaysia. This research represented a qualitative approach, using the case study method and was conducted based on the CEO of Company ABC. A semi-structured interview with the CEO of Company ABC was conducted to gain an in-depth understanding on the aspects that this research covers. This interview also enable to obtain opinions from the CEO of Company ABC on his experiences and perceptions. The main purpose of this study is to find out what are the main factors that improve the Malaysian firms' productivity in E&E industry, to find out the issues and challenges faced by Malaysian firms, and the impact of fourth industry revolution towards the performance and productivity of Malaysian firms in E&E industry. Results and findings were obtained using a semi-structured interview, which were then compared against the literature review from previously written journals. Recommendations and conclusions were drawn at the end of this research project.